Students' Perception of Socio-Affective Impacts of Translanguaging in EFL Classroom - Adam, Sutisno; Lustyantie, Ninuk; Murtadho, Fathiaty (LPPM Institut Pendidikan Nusantara Global, 2025)
This qualitative study explores students' perceptions of translanguaging in the English as a Foreign Language (EFL) classroom context at Universitas Khairun. Drawing on semi-structured interviews with three undergraduate students, this research examines the roles, benefits, and challenges of using multiple languages (English, Bahasa Indonesia, and Melayu Ternate) in the classroom. Findings reveal that varying emotional responses, such as pride, confusion, and self-consciousness, emerge as translanguaging effects. Triangulation with faculty perspectives confirms translanguaging as an inclusive, efficient, and strategic pedagogical practice. The study concludes that translanguaging is a beneficial approach in multilingual EFL contexts to support deeper engagement and understanding.